Left ventricle ejection fraction and strain derived by three-dimensional echocardiography are associated with exercise capacity in the patients with heart failure - Pavlovic-Kleut, Milena; Sljivic, Aleksandra; Celic, Vera (Vojnosanitetski pregled, 2021)
Background/Aim. Echocardiography represents the most commonly performed noninvasive cardiac imaging tests for the patients with heart failure (HF). The aim of this study was to assess the relationship between the exercise capacity parameters [peak oxygen consumption (VO2) and the minute ventilation-carbon dioxide production relationship (VE/VCO2)] and the three-dimensional speckle-tracking echocardiography (3D-STE) imaging of left ventricular (LV) function in the HF patients with the reduced LV ejection fraction (LVEF). Methods. This cross-sectional study included 80 patients with diagnosed ischemic LV systolic dysfunction (LVEF < 45%) divided into subgroups based on the proposed values of analyzed cardiopulmonary exercise testing (CPET) variables: VO2 peak ≤ 15 mL/kg/min, VO2 peak > 15 mL/kg/min, VE/VCO2 slope < 36 and VE/VCO2 slope ≥ 36. All patients underwent a physical examination, laboratory testing, two-dimensional (2D) and 3DE, and CPET. Results. LVEF, global longitudinal, circumferential, radial and area strains were significantly lower in the subgroups of subjects with a peak VO2 less, or equal to 15 mL O2/kg per min and with a VE/VCO2 slope greater, or equal to 36 compared to the subgroups of subjects with a peak VO2 greater than 15 mL O2/kg per min and with a VE/VCO2 slope less than 36. There was a significantly positive correlation between the peak VO2 values and parameters of 3DE, and a significantly negative correlation between the VE/VCO2 slope values and parameters of 3DE. Conclusion. The results of this study provide further evidence that the LV function can be noninvasively and objectively measured by 3D-STE. A significant correlation between examined parameters suggests that LVEF and strain derived by 3DE are associated with exercise capacity in the patients with HF.